The Effect of Foliar Spray by Boron on Yield and Fruit Quality of Var. AL Khelkhaly Olive Tree. (Journal of Hama University, 2019)
The aim of this research is to study the number and time of foliar spray by Boron chelate amino acids to its effect on the fruit set and yield var. (Al Khelkhaly). This research is implemented in cultivated field planted with olive trees in town (Komhana- Hama, province). The trees which are chosen are similar in size and free from disease and insect.The application of foliar spray by boron chelate a mino Asids concentrate (350 ppm B) according to these application. The first application: the control leave without foliar spray. The second application: the spray by boron one time before flowering. The third application: the spray by boron two times before flowering and after fruit set. The fourth application: the spray by boron three times before flowering- after fruit set and during the pit hardening. The fifth application: the spray by boron four times before flowering- after fruit set- during the pit hardening and at the end of summer.The result demonstrates that there is no significant difference on the average of number of inflorescence on a branch and the complete number of flower on the branch. Hearse that boron affect positively the percentage of perfect flowers that the average of application reaches to (% 75.98) whereas in the control (66.83 %) and also on the fruit set that the average of the fruit set reaches to (7.68 %) and in the control (4.98 %%).These application of foliar spray by Boron manifest the increase of tree production especially when we applied the application for two time the average of the third application reaches (27.6 Kg/ tree) where in the control (16.8 Kg/ tree), and also in morphological specification especially in the fifth application (for times spray by boron) the Weight of fruit (2.87 g) and in the control (2.13 g).All treatments  of boron didn't effect on length shoots growth .